Recycling method of negative electrode main material of lithium battery, negative electrode main material and battery

Through a method for recycling the negative electrode main material of lithium battery, including pickling, high-temperature burning and magnetic separation, the problem of impurity removal during the recycling process is solved, and the performance of graphite is improved, so that when the graphite is recovered for the preparation of the battery, the capacity retention rate and the number of cycles are significantly improved.

CN119797358APending Publication Date: 2025-04-11HUBEI SHUANGDENG ENERGY STORAGE TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411911530.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove organic impurities introduced during lithium battery recycling, and the graphite performance obtained from the recovery has not been improved, resulting in poor capacity retention and cycle times of lithium-ion batteries.

Method used

A method for recycling the main material of lithium battery negative electrode is adopted, including collecting the negative electrode powder in the lithium battery production process, performing pickling, filtration, drying, high-temperature burning, magnetic separation and screening, and removing impurities through these steps to improve the performance of graphite.

Benefits of technology

The organic impurities introduced during the recycling process are effectively removed, and the surface adhesion area and purity of the graphite are improved, so that the batteries prepared from the recycling graphite have a higher capacity retention rate and a longer cycle number.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797358A_ABST
    Figure CN119797358A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium battery negative electrode main material recovery method, a negative electrode main material and a battery, and relates to the technical field of battery recovery, the lithium battery negative electrode main material recovery method comprises the following steps: S1, collecting negative electrode powder in a lithium battery production process; s2, the negative electrode powder is filtered and dried after being subjected to acid pickling, and primary powder is obtained; s3, the primary powder is subjected to high-temperature firing and then sieved, secondary powder is obtained, the high-temperature firing temperature is set to be 600-1000 DEG C, and the high-temperature firing time is set to be 2-4 h; s4, magnetic metal impurities in the second-stage powder are removed through magnetic separation, and third-stage powder is obtained; and S5, sieving and drying the third-stage powder to obtain final powder. The recovery method provided by the invention is simpler to operate, new impurities introduced in the recovery process can be removed under the condition of low recovery environment requirements, and the battery prepared from the recovered graphite has a higher capacity retention ratio compared with a normal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery recycling, and in particular to a method for recycling a negative electrode main material of a lithium battery, graphite and a battery. Background Art

[0002] Graphite occupies a dominant position in the negative electrode materials of commercial lithium batteries due to its outstanding physical and chemical properties and structural advantages. Currently, lithium-ion batteries use graphite as the main negative electrode material, with polyacrylic acid and styrene-butadiene rubber as binders. Due to the material system, the active material is easy to fall into powder (i.e. graphite powder) during the manufacturing process.

[0003] Specifically, there are currently multiple key processes in the production of lithium batteries (such as mixing, coating, rolling, etc.), and graphite powder falls in each of the above processes. For the fallen graphite powder, the relevant technology uses ultrasonic dust removal and negative pressure dust suction methods to collect the powder and then scrap it, making this part of the negative electrode main material unable to be recycled, and the loss of graphite powder in the production process is relatively large.

[0004] This is because, when the fallen graphite powder is collected, organic impurities such as grease, hair, dandruff and straw are usually further introduced. The recycling of graphite powder in related technologies is still limited to dismantling used lithium batteries, removing the negative electrode materials from them, and then grinding and pickling them. This method cannot effectively remove the organic impurities introduced during the collection process, and the performance of the collected graphite cannot be improved.

[0005] In view of this, there is an urgent need to provide a recycling method that can effectively remove new impurities introduced during the recycling process and improve the performance of graphite powder. Summary of the invention

[0006] The present application provides a method for recycling the main material of the negative electrode of a lithium battery, which can recycle graphite. The operation is simple and the organic impurities introduced during the recycling process can be effectively removed. The battery prepared using the recycled graphite has a higher capacity retention rate than a normal battery.

[0007] In a first aspect, the present application provides a method for recycling a negative electrode main material of a lithium battery, comprising the following steps:

[0008] S1. Collect negative electrode powder in the production process of lithium batteries;

[0009] S2, acid-washing the negative electrode powder, filtering and drying it to obtain a primary powder;

[0010] S3, high-temperature calcining the primary powder and then sieving it to obtain a secondary powder, wherein the high-temperature calcination temperature is set to 600-1000° C., and the high-temperature calcination time is set to 2-4 hours;

[0011] S4, magnetic separation to remove magnetic metal impurities in the secondary powder to obtain tertiary powder;

[0012] S5, sieving and drying the three-level powder to obtain the final powder.

[0013] By adopting the above scheme, the negative electrode main material is ground into powder to obtain negative electrode powder, and the obtained negative electrode powder can be collected by a simple collection tool (such as a brush). The entire recycling process can also better remove magnetic metal impurities in the negative electrode powder under the premise of low requirements on the environment and equipment, and further remove organic impurities introduced in the recycling process, such as grease, hair, dandruff and straw;

[0014] Inorganic waste formed by burning organic impurities is removed after screening. The entire recycling method is simple to operate, and the performance of the negative electrode main material recovered by the method is further improved, so that the battery prepared by the recycled negative electrode main material has a higher capacity retention rate.

[0015] Specifically, the internal structure of the primary powder treated at high temperature becomes more uniform, providing a larger surface attachment area, which is conducive to the insertion and extraction of lithium ions during the electrochemical reaction. In addition, the burning temperature can be set according to the actual equipment conditions. In one embodiment, the burning temperature can be set to 600 degrees, 800 degrees or 1000 degrees.

[0016] Further, the S2 includes:

[0017] Rinse the negative electrode powder with pure water 2 to 3 times;

[0018] The negative electrode powder and the acidic solution are stirred and mixed to obtain a primary mixed solution, wherein the stirring temperature is set to 25 to 45° C. and the stirring time is set to 2 to 4 hours.

[0019] By adopting the above scheme, pure water washing can remove some non-target impurities on the surface of the negative electrode powder, such as conductive agents, adhesives, etc., that is, some easily removable impurities can be removed in advance to facilitate subsequent acid washing and filtration of primary powder.

[0020] Furthermore, the acidic solution includes at least one of a sulfuric acid solution, a hydrochloric acid solution, a nitric acid solution or a chloric acid solution.

[0021] By adopting the above scheme, the magnetic metal impurities in the negative electrode powder are dissolved. In one embodiment, the acidic solution uses a 0.5% by mass dilute sulfuric acid solution, which has a low cost. Dilute sulfuric acid, as a binary strong acid, can better dissolve the magnetic metal impurities.

[0022] Furthermore, before S4, the method further includes detecting the content of magnetic metal impurities in the secondary powder;

[0023] If the content of magnetic metal impurity elements accounts for ≥1% of the secondary powder, repeat steps S1 to S3;

[0024] If the content of magnetic metal impurity elements in the secondary powder is less than 1%, proceed to the next step.

[0025] After pickling, a small amount of magnetic metal impurities will still remain in the powder. These metal impurities will affect the self-discharge performance of the battery. By adopting the above scheme, a scanning electron microscope is used to perform EDS analysis on the secondary powder to detect the proportion of each element in the secondary powder. Among them, if the element proportion of the magnetic metal impurities is higher than the set requirement, it means that the magnetic metal impurities were not well dissolved during the pickling of the powder. At this time, S2 is re-executed to ensure that the content of the magnetic metal impurities meets the requirements.

[0026] Furthermore, before S4, the method further includes detecting the content of magnetic metal impurities in the secondary powder;

[0027] If the content of magnetic metal impurity elements accounts for ≥1% of the secondary powder, repeat steps S2 to S3;

[0028] If the content of magnetic metal impurity elements in the secondary powder is less than 1%, step S4 is performed.

[0029] By adopting the above scheme, the powder is subjected to high-temperature burning while pickling again, which can effectively remove the acid solution residue in the pickling process, so as to reduce the probability of further introducing impurities during the second pickling.

[0030] Furthermore, the magnetic separation to remove magnetic metal impurities in the secondary powder includes: continuously stirring the secondary powder by a magnetic bar, the stirring time of the magnetic bar is set to 5 to 15 minutes, and the adsorption strength of the magnetic bar is ≥12000GS.

[0031] By adopting the above scheme, before the content of magnetic metal impurity elements accounts for less than 1% of the secondary powder, the magnetic metal impurity elements in the secondary powder are further removed, so that the final magnetic metal impurity mass accounts for 0-0.3% of the secondary powder. In one embodiment, the stirring time can be set to 5 minutes, and the magnetic rod adsorption strength is set to 15000GS. In another embodiment, the stirring time can also be set to 10 minutes or 15 minutes, and the magnetic rod adsorption strength is set to 12000GS.

[0032] In a second aspect, the present application provides a graphite obtained by the above-mentioned recovery method.

[0033] By adopting the above scheme, the obtained graphite has low impurity content, larger surface area and more excellent performance.

[0034] In a third aspect, the present application provides a battery comprising graphite obtained by the above-mentioned recycling method.

[0035] By adopting the above scheme, the capacity retention rate and cycle number of the battery prepared by using recycled graphite are improved.

[0036] In summary, the present application includes at least one of the following beneficial technical effects:

[0037] 1. Under the premise of low requirements on the environment and equipment, the recycling method in this application can effectively remove magnetic metal impurities in the negative electrode powder and further remove organic impurities introduced in the recycling process. The operation is simple, and the performance of the graphite recovered by this method is further improved, so that the battery prepared by the recycled graphite has a higher capacity retention rate.

[0038] 2. In the present application, the powder is purified by high-temperature calcination, which will burn off organic impurities introduced in the process of collecting the negative electrode powder, such as grease, hair, dandruff and straw, and the internal structure distribution of the treated powder is more uniform, which can increase the adhesion area compared to normal graphite, and is beneficial to the embedding and extraction of lithium ions in the electrochemical reaction process.

[0039] 3. In this application, after the powder is pickled, an EDS scan is performed on the powder to detect magnetic metal impurities in the powder. If the element ratio of the magnetic metal impurities is higher than the set requirements, it means that the magnetic metal impurities were not well dissolved during the pickling of the powder. At this time, S2 to S3 are re-executed. If the element ratio of the magnetic metal impurities meets the set requirements, the trace magnetic metal impurities in the powder are further removed by magnetic separation, thereby ensuring the purity of the prepared graphite. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a schematic diagram of the proportion of each element in normal graphite;

[0041] Figure 2 It is a schematic diagram of the proportion of each element in the recycled graphite;

[0042] Figure 3 This is the microscopic morphology of normal graphite;

[0043] Figure 4 It is a microscopic morphology of recycled graphite;

[0044] Figure 5 This is a comparison chart of battery cycle data of normal graphite and recycled graphite. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical solutions and advantages of this application more clear, the following Figure 1-5 It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0046] Those skilled in the art will appreciate that, unless otherwise stated, the words "said", "the", and "the aforementioned" used in the text of the present application may also include plural forms. It should be further understood that the wording "including" used in the specification of the present application means the presence of the features, steps, and operations, but does not exclude the presence or addition of one or more other features, integers, and steps.

[0047] Those skilled in the art will appreciate that, for any specific experimental steps or conditions not specified in the examples, the experiments may be carried out according to the conventional experimental steps or conditions described in the literature in the art; any raw materials or instruments used without specifying the manufacturer are conventional products that can be purchased commercially.

[0048] Those skilled in the art will understand that, unless otherwise specified in the present application, when a numerical range is given in an embodiment, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this application are consistent with the prior art mastery of those skilled in the art and the records of this application, and any methods, equipment and materials of the prior art similar or equivalent to the methods, equipment and materials described in the embodiments of this application may also be used to implement this application.

[0049] Embodiment 1:

[0050] A method for recycling a lithium battery negative electrode main material comprises the following steps:

[0051] 1) Collect negative electrode powder during the production process of lithium batteries;

[0052] 2) 50 kg of negative electrode powder was washed with pure water for 3 times, then mixed with 50 kg of 0.5% mass fraction dilute sulfuric acid, washed for 3 hours at 25° C. with a stirring speed of 25 rpm and 1200 rpm, and cooled to room temperature to obtain a mixed solution;

[0053] 3) filtering the mixed solution, washing and drying the filtrate to obtain a primary powder;

[0054] 4) The primary powder is placed in a porcelain crucible and placed in a muffle furnace, heated to 600°C ± 50°C and burned for 3 hours; after cooling to room temperature, it is sieved through a 300-mesh sieve to obtain a secondary powder;

[0055] 5) Perform EDS analysis on the secondary powder using a scanning electron microscope. If the proportion of magnetic metal impurity elements in the secondary powder is less than 1%, proceed to the next step. If the proportion of magnetic metal impurity elements in the secondary powder is ≥ 1%, repeat steps 2-3.

[0056] 6) Place the secondary powder in a stainless steel container and stir it clockwise for 15 minutes using a magnetic bar with a diameter of 5 cm and a length of 50 cm and a magnetic strength of 12000 GS to remove magnetic metal impurities in the secondary powder to obtain a tertiary powder.

[0057] 7) The third-grade powder is sieved through a 200-mesh sieve, and the third-grade powder is dried at 120° C. for 24 h under a vacuum condition of -95 KPa to obtain the final powder (i.e., the negative electrode main material, also known as recovered graphite).

[0058] Embodiment 2:

[0059] A method for recycling a lithium battery negative electrode main material is the same as that of Example 1, except that the burning temperature in step 3) is set to 800°C±50°C.

[0060] Embodiment 3:

[0061] A method for recycling a lithium battery negative electrode main material is the same as that of Example 1, except that the burning temperature in step 3) is set to 1000°C±50°C.

[0062] Embodiment 4:

[0063] A method for recycling a lithium battery negative electrode main material is the same as that of Example 1, except that the burning time in step 3) is set to 2 hours.

[0064] Embodiment 5:

[0065] A method for recycling a lithium battery negative electrode main material is the same as that of Example 1, except that the burning time in step 3) is set to 4 hours.

[0066] Embodiment 6:

[0067] A method for recycling the main material of the negative electrode of a lithium battery is the same as that of Example 1, except that after the mixed solution is filtered to obtain the primary powder, a 10% mass fraction NaOH solution is added to the remaining solution (i.e., the secondary mixed solution) to adjust the pH to neutral.

[0068] Embodiment 7:

[0069] A method for recycling a lithium battery negative electrode main material is the same as Example 1, except that a scanning electron microscope is used to perform EDS analysis on the secondary powder. If the proportion of magnetic metal impurity elements in the secondary powder is less than 1%, the next step is performed. If the proportion of magnetic metal impurity elements in the secondary powder is ≥ 1%, steps 2-4 are repeated.

[0070] Embodiment 8:

[0071] A method for recycling the negative electrode main material of a lithium battery is the same as Example 1, except that the negative electrode powder comes from waste lithium batteries, and obtaining the negative electrode powder includes the following steps: disassembling the negative electrode material of the waste lithium battery, grinding the negative electrode material, and obtaining the negative electrode powder.

[0072] Comparative Example:

[0073] A normal graphite, purchased from Dalian Hongguang New Energy Materials Co., Ltd., is used for the preparation of batteries and is of the same batch as the recycled graphite model collected in Example 1.

[0074] Experiment 1:

[0075] The recovered graphite and normal graphite obtained in Example 1 were analyzed by EDS using a scanning electron microscope, and the proportions of each element in the normal graphite were obtained as shown in Table 1. Figure 1 As shown in Table 2, the proportions of each element in the recycled negative electrode main material (i.e., recycled graphite) are shown in Table 2. Figure 2 shown.

[0076] Table 1

[0077] element Line Type Wt% Wt%Sigma At% C K-line system 91.37 0.37 93.38 O K-line system 8.62 0.37 6.62 Si K-line system 0.01 0.03 0.01 Total 100 100

[0078] Table 2

[0079]

[0080]

[0081] Among them, the Figure 1 , Figure 2 The horizontal axis represents energy. The characteristic X-rays emitted by different elements have different frequencies (that is, different energies). The vertical axis represents the X-ray counts. The intensity value is related to the element content, that is, the higher the element content, the larger the corresponding vertical axis value.

[0082] It can be found that the magnetic metal impurity elements in the recycled graphite have been well removed, and the proportion of each element content in the recycled graphite is almost the same as that in normal graphite (the oxygen element mainly comes from the air, and there are certain test fluctuations), which means that the recycled graphite can be further put into production.

[0083] Experiment 2:

[0084] The recovered graphite and normal graphite obtained in Example 1 were scanned by a scanning electron microscope, and the microscopic morphologies of the recovered graphite and normal graphite were obtained as follows: Figure 3 , Figure 4 shown.

[0085] It can be found that some tissues of normal graphite are distributed in a disorderly and uneven manner, and the particle sizes are different. Compared with normal graphite, the surface of recycled graphite is clearer, the distance between adjacent tissues is larger, the tissue distribution is more dispersed, and the particle size distribution is more uniform.

[0086] This is because the microstructure of graphite is changed during the high-temperature burning process, so that the surface adhesion area provided by the recycled graphite is higher than that of normal graphite, which provides a larger area for the insertion and extraction of lithium ions during the electrochemical reaction.

[0087] Experiment 3:

[0088] The recycled graphite obtained in Example 1 was used to prepare a battery, and the battery was tested with a normal battery prepared from normal graphite to obtain a battery cycle data comparison curve of normal graphite and recycled graphite. Figure 5 shown.

[0089] It can be found that the capacity retention rate of the experimental group is higher than that of the control group, and with the increase in the number of cycles, the gap in capacity retention rate between the experimental group and the control group is gradually increasing, which shows that the performance of the battery prepared with recycled graphite is further improved compared with ordinary batteries.

[0090] This is because recycled graphite has a larger surface attachment area and attachment space than normal graphite, which is more conducive to the insertion and removal of lithium ions during the charging and discharging process. At the same time, the magnetic metal impurities in recycled graphite are less than those in normal graphite, further reducing the self-discharge rate of the battery.

[0091] In summary, the recycling method in this application can recycle graphite, its operation is simpler, and the requirements for the recycling environment are low. The battery prepared using recycled graphite has a higher capacity retention rate than normal batteries. It effectively improves the utilization rate of resources and has a good application scenario.

[0092] The embodiments of this specific implementation are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. The same components are represented by the same figure marks. Therefore, any equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A method for recycling the negative electrode main material of a lithium battery, characterized in that: The following steps are involved: S1. Collect negative electrode powder in the production process of lithium batteries; S2, acid-washing the negative electrode powder, filtering and drying it to obtain a primary powder; S3, high-temperature calcining the primary powder and then sieving it to obtain a secondary powder, wherein the high-temperature calcination temperature is set to 600-1000° C., and the high-temperature calcination time is set to 2-4 hours; S4, magnetic separation to remove magnetic metal impurities in the secondary powder to obtain tertiary powder; S5, sieving and drying the three-level powder to obtain the final powder.

2. The recycling method according to claim 1, characterized in that: The pickling comprises: Rinse the negative electrode powder with pure water 2 to 3 times; The negative electrode powder and the acidic solution are stirred and mixed to obtain a primary mixed solution, wherein the stirring temperature is set to 25 to 45° C. and the stirring time is set to 2 to 4 hours.

3. The recycling method according to claim 2, characterized in that: The acidic solution includes at least one of a sulfuric acid solution, a hydrochloric acid solution, a nitric acid solution or a chloric acid solution.

4. The recycling method according to claim 1, characterized in that: Before S4, it also includes detecting the content of magnetic metal impurities in the secondary powder; If the content of magnetic metal impurity elements accounts for ≥1% of the secondary powder, repeat step S2; If the content of magnetic metal impurity elements in the secondary powder is less than 1%, step S4 is performed.

5. The recycling method according to claim 4, characterized in that: Before S4, it also includes detecting the content of magnetic metal impurities in the secondary powder; If the content of magnetic metal impurity elements accounts for ≥1% of the secondary powder, repeat steps S2 to S3; If the content of magnetic metal impurity elements in the secondary powder is less than 1%, step S4 is performed.

6. The recovery method according to claim 1, 4 or 5, characterized in that: The magnetic separation to remove magnetic metal impurities in the secondary powder includes: stirring the secondary powder by a magnetic rod, the stirring time is set to 5 to 15 minutes, and the adsorption strength of the magnetic rod is ≥12000GS.

7. A negative electrode main material, characterized in that: The negative electrode main material is obtained by the recycling method according to any one of claims 1 to 6.

8. A battery, characterized in that: The battery comprises the negative electrode main material according to claim 7.